The effect of transference of cattle with periodontal disease (cara inchada) to pastures in a helthy region - Döbereiner, Jürgen; Chaves, Jerônimo Alves; Rosa, Ivan Valadão; Houser, Richard H. (Pesquisa Agropecuaria Brasileira, 2014)
A group of 34 mostly young cattle, affected by the periodontal disease called “cara inchada” (Swollen face) and in bad condition, was transferred from a region where the disease occurs to a farm situated in a healthy region. Half of the cattle survived in spite of their ill health and the adverse conditions of a prolonged draught. Clinical examinations of the buccal cavity of these animals revealed a regression of the periodontal lesions after only 2 months and, in a certain way, a cure of the lesions after 4 to 6 months. Most of the animals improved their condition considerably and their haircoat became less rough. At the beginning and the end of the experiment, four animals were sacrificed for dose macroscopic examination and comparison of the periodontal changes and to collect liver samples for future chemical analyses. The clinical and anatomo-pathological findings in this experiment strengthen the hypothesis that the etiology of "cara inchada" is related to one or more alimentary factors present in the regions where the disease occurs.